Drug use and delinquency : causes of dropping out of high school? - Gasper, Joseph M., 1980- (Criminal justice (LFB Scholarly Publishing LLC), 2012)
"Gasper examines whether drug use and delinquency contribute to early school leaving and whether the effects differ for poor and middle-class youth. Results suggest that drug use and delinquency add little to explanations of dropout. Rather, drug use, delinquency, and dropout are driven by a process of precocious development rooted in early school failure. Driven by a fundamental dissatisfaction with school, precocious teens are more likely to use drugs, take on a job outside of school, and leave school without a diploma in an effort to gain independence. Dropout prevention should start in middle or elementary school and attempt to interrupt the developmental cycle of failure and problem behavior that culminates in dropout."--Publisher's description.